2020
DOI: 10.3390/ijms21124435
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of B3 and D8 Measles Viruses through Hemagglutinin Phylogenetic History

Abstract: Of the 24 known measles genotypes, only D8 and B3 are responsible for outbreaks in the last years in Europe, Asia, and America. In this study the H gene of 92 strains circulating between 2015 and 2019 in Lombardy, Northern Italy, and 1273 H sequences available in GenBank were analyzed in order to evaluate the genetic variability and to assess the conservation of the immunodominant sites. Overall, in Lombardy we observed the presence of four different B3 and three different D8 clusters, each one of them includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 45 publications
(89 reference statements)
6
11
0
1
Order By: Relevance
“…The collection time also revealed that these three clades circulated almost alternately, and that the sub-genotype 3.2/400V clade was the only variant circulating globally in the past decade. Similar results were also observed by Bianchi et al [19]. In a comparison of neutralizing antibody titers against outbreakassociated measles genotypes (D4, H1, and B3) in Iran, the lowest geometric mean titer of antibodies against B3 was observed [35].…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The collection time also revealed that these three clades circulated almost alternately, and that the sub-genotype 3.2/400V clade was the only variant circulating globally in the past decade. Similar results were also observed by Bianchi et al [19]. In a comparison of neutralizing antibody titers against outbreakassociated measles genotypes (D4, H1, and B3) in Iran, the lowest geometric mean titer of antibodies against B3 was observed [35].…”
Section: Discussionsupporting
confidence: 88%
“…The 2.5% and 2.0% nucleotide divergences in the MeV N and H genes, respectively, were used to define a new MeV genotype by the WHO criteria [30]. In this study, the results of phylogenetic analysis revealed two main sub-genotypes (3.1 and 3.2) of MeV B3's H gene, as reported previously [19,31,32], and the minimum genetic distance between the proposed B3 sub-genotypes (1.51%) did not match the 2.0% diversity threshold for assigning a new genotype. Based on the N450 gene, MeV B3 can be divided into three lineages [33,34].…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations